Effect of Drying Temperature to the Thin Layer Drying Model of Sago Starch - Maswida, Mustafa Kamal; Rubiyah, Baini; Lim, Soh Fong; Mohd Hasnain, Md Hussain; Shahrol, Mohamaddan (2020)
The demand on sago starch in industrial application is continuously grow-ing, but the research on its drying behavior is still limited. In this study, ten thin layerdrying models were compared through four drying temperatures in order to find thebest model to describe the drying characteristic of sago starch. According to theresults, sago starch exhibits drying during the falling rate period. The moisture dif-fusivities ranged from 8.56×10−10to 1.39×10−9m2/s that varied through dryingtemperature while the activation energy was 16.18 kJ/mol. Based on the study, thedrying pattern was best described by the Page model.